Acute Urinary Retention: A Rare Presentation in Acute Myeloid Leukemia - Barik, Sumit; Sinha, Sweta (International Journal of Medical Research and Review, 2014)
Hyperleukocytosis is defined when the total leukocyte count is more than 100000/cmm. Leukostasis occurs in hyperleukocytic acute myeloid leukemia when the numbers of blasts are very high. Leukostasis causes impaired normal functioning of vascular systems because of crowding of blasts in its microvasculature or in its vessels supplying the nerves. Leukostasis causes early deaths in acute myeloid leukemia (AML) due to involvement of central nervous system and lungs. Acute retention of urine because of haematological causes is rarely seen. Dysfunction of bladder because of leukostasis in hyperleukocytic AML is warning. Cytoreduction therapy in hyperleukocytic AML prevents early deaths.